Xenophobia and anti-immigrant attitudes in the time of COVID-19. (February 2021) - Esses, Victoria M.; Hamilton, Leah K.
The devastating impact of the COVID-19 pandemic on nations and individuals has almost certainly led to increased feelings of threat and competition, heightened uncertainty, lack of control, and a rise in authoritarianism. In this paper we use social psychological and sociological theories to explore the anticipated effects on xenophobia and anti-immigrant attitudes worldwide. Based on our analysis, we discuss recommendations for further research required during the ups and downs of the pandemic, as well as during recovery. We also discuss the need for research to address how to best counteract this expected surge in xenophobia and anti-immigrant attitudes. As the pandemic persists, it will be important to systematically examine its effects on xenophobia and anti-immigrant attitudes, and to develop and implement strategies that keep these negative attitudes at bay.